3D soft auxetic lattice structures fabricated by selective laser sintering: TPU powder evaluation and process optimization. (15th April 2017) - Yuan, Shangqin; Shen, Fei; Bai, Jiaming; Chua, Chee Kai; Wei, Jun; Zhou, Kun
Abstract: The auxetic foams composed of highly porous thermoplastic polyurethane (TPU) exhibit an attractive behaviour of withstanding a large volume reduction upon the cyclic compressive loading. A family of three-dimensional (3D) artificial metamaterials via Bucklicrystals consisting of an array of elastomeric spherical shells with periodical lattice patterns were proposed to mimic the buckling-induced auxetic behaviour as TPU foams. Layer-by-layer deposition of the desirable materials to manufacture parts known as additive manufacturing enables to create complex geometries and provides the broad freedom in design and manufacturing. In this work, selective laser sintering offered a unique capability to fabricate tailorable and flexible 3D soft metamaterials using TPU powders. An effective method was proposed to systematically evaluate the TPU powders and optimize the fabrication process, in order to overcome the challenges of sintering the duel-segment TPU. The laser-sintered Bucklicrystals were highly recoverable undergoing repeated compressions, and they retained the auxetic properties over a wide range of applied deformations. The fabrication of 3D soft metamaterials is not constrained by existing manufacturing principles and the laser-sintered Bucklicrystals of TPU are highly valuable to various engineering applications, such as mechanical and acoustic energy absorbers, actuators and vibration-resistant dampers. Graphical abstract: Highlights: The systematic approach of powder evaluation and process optimization was proposed for the SLS system. The 3D soft auxetic lattice structures were successfully fabricated by selective laser sintering of thermoplastic polyurethane. The 3D-printed soft metamterials with negative Poisson ratios are capable of retaining such unusual deformations at large strains and withstanding repeated compression cycling of deformations.